Dianthin-EGF is an effective tumor targeted toxin in combination with saponins in a xenograft model for colon carcinoma. (November 2014) - Mallinckrodt, Benedicta von; Thakur, Mayank; Weng, Alexander; Gilabert-Oriol, Roger; Dürkop, Horst; Brenner, Winfried; Lukas, Mathias; Beindorff, Nicola; Melzig, Matthias F; Fuchs, Hendrik
ABSTRACT : Aims: The intention of this work was to lift saponin supported tumor targeted therapies onto the next level by using targeted toxins in nude mice xenotransplant models.Materials & methods: Combined application of dianthin coupled to EGF and saponin SO-1861 was tested in a xenograft model of colon carcinoma. In vitro cytotoxicity was tested in real-time in NIH3T3 cells (no human EGF receptor expression), HER14 and human colon carcinoma HCT116 (both EGF receptor overexpressing) cells. A xenograft model was established using HCT116 cells and tumor-bearing animals were treated with SO-1861 (30 µg/treatment) and dianthin coupled to EGF (0.35 µg/treatment). Tumor progression was monitored, using 18 F-2-fluor-2-desoxy-d -glucose, by small animal PET and by x-ray computed tomography.Results: In vitro results demonstrated a high-receptor specificity and the in vivo experiment showed a progressive reduction of the tumor volume and glycolytic activity in the treated group (>95% reduction; p < 0.05).Conclusion: This therapy has great advantage because of high specificity, low side effects and great effectiveness for future development in the treatment of colon cancer.